FACULTY OF PHYSICAL EDUCATION AND SPORTS: HISTORY AND MODERN REALITIES - Коробейнік, В.; Кравчук, Т. (New Collegium, 2020)
The first attempts to train teachers in physical education were made as early as 1925. In 1930, the Department of Physical Culture at HINO was liquidated and the State Institute of Physical Culture of Ukraine was opened on its basis. In 1947 the Faculty of Physical Education and Sports was opened at the Kharkov State Pedagogical Institute named after GS Skovoroda. The main task of the management and teachers was to conduct a high-quality set of entrants and to organize educational work with students. During the years of the faculty's existence, more than 9000 physical education teachers were trained in full-time and part-time forms of study. Among the students of the faculty — five Olympic champions, champions and prize-winners of the World, Europe and Ukraine, more than 80 became honored coaches. The modern faculty is capable of guaranteeing the training of qualified specialists of Bachelor's, Master's degrees in the specialties 014 "Secondary Education (Physical Education)" and 017 "Physical Education and Sports"